Klarspråksledelse – mer enn gode tekster - Aanestad, Onar (Klart språk i Norden, 2015)
Fra 2009 til 2012 gjennomførte Statens pensjonskasse (SPK) en stor satsing på klarspråk. Vi forbedret mer enn 300 brev, forenklet alt innhold på nett og laget informasjon om pensjonsreformen i klarspråk. Arbeidet ble belønnet med Klarspråksprisen 2011. Prosessen var langt fra knirkefri. For SPK ble klarspråksledelse nøkkelen for å lykkes med klarspråk. Denne artikkelen prøver å forklare hva vi lærte. Summary The Norwegian Public Service Pension Fund (SPK) learned many lessons during its work on plain language from 2009 to 2012. One of them was that leadership was needed to overcome challenges and create results. SPK improved more than 300 letters, changed all the content on the web and used plain language to explain the pension reform to our one million members and their 1,600 employers. SPK won the Plain Language Award in 2011. The process was not easy. Leadership became the key to making plain language possible. In this article we share our experience and lessons learnt.